Crafting the Alternative of Finance Hegemony: Returning Gold Dinar Exchange Economy - Poppy Irawan (Department of International Relations, Universitas Andalas)
The aim of this paper is to examine the contemporary issues of global political economy on the predominance of finance capital as the pivotal role in moulding the current global political economy architecture; its impact particularly to the developing states; and this paper also attempt to propose the alternative through the returning of gold monetary system based on the idea of gold dinar exchange economy.